A lattice Boltzmann study of the asymmetry effect on the hemodynamics in stented fusiform aneurysms. (January 2016) - Wang, Lei; Shi, Baochang; Chai, Zhenhua
Abstract: In this paper, the effect of asymmetric bulges on the hemodynamics in stented fusiform aneurysms under pulsatile Newtonian flow condition has been studied numerically by the lattice Boltzmann method. In order to guarantee the efficiency and accuracy of the method, a domain decomposition technique is also considered. Numerical results show that the flow structures are significantly affected by the asymmetric bulges. For non-stented fusiform aneurysms, the maximum wall shear stress (WSS) and maximum wall pressure are found to occur near the distal end of the aneurysms at peak systole, and the magnitude of peak WSS and wall pressure usually increase along with the increase of the maximum height of the dilated region. In addition, the implantation of a stent can reduce the magnitude of the maximum wall pressure and WSS at the distal end, and a low-porosity stent gives better performance than a high-porosity stent in terms of the reduction. In particular, for stented fusiform aneurysms, the effect of asymmetry on wall pressure is found insignificant. Further, a comparison between pulsatile solution and steady-state solution at peak systole is also presented, and the results show that the difference of WSS near the proximal neck for two conditions is not apparent, while the location of the maximum wall pressure obtained from steady-state condition moves toward downstream in contrast to pulsatile condition, and the maximum WSS at the distal end is underestimated by the condition of steady-state.